Brachial-Ankle Pulse Wave Velocity Is the Only Index of Arterial Stiffness That Correlates with a Mitral Valve Indices of Diastolic Dysfunction, but No Index Correlates with Left Atrial Size. (6th March 2013) - Chow, Bryan; Rabkin, Simon W.
Abstract : The objective of this study was to determine the optimal assessment of arterial stiffness that relates to diastolic dysfunction. Forty-one patients had measurements of brachial-ankle pulse wave velocity (baPWV), carotid-femoral pulse wave velocity (cfPWV), ankle brachial index (ABI), pulse pressure (PP), and augmentation index (AIx). Diastolic dysfunction was evaluated by echocardiographic indices of the ratio of the peak early diastolic mitral valve velocity and the peak late diastolic velocity ( E/A ratio), left atrial diameter, and left atrial volume indexes. There was a significant (P < 0.05 ) correlation between baPWV and E/A ratio with an inverse relationship indicating that higher arterial stiffness was associated with greater diastolic dysfunction. In contrast, there was no significant correlation between E/A ratio and cfPWV, PP, ABI, or AIx. After multivariate analysis, the relationship between baPWV and E/A ratio remained significant (P < 0.05 ), independent of age and systolic blood pressure (BP). There were no correlations between any index of vascular stiffness and left atrial dimension or volume. In summary, baPWV correlates with diastolic dysfunction, independent of a patient's age and BP and is a better indicator of diastolic dysfunction than other indicators of arterial stiffness. baPWV has the utility of infering the presence of left ventricular diastolic dysfunction.